2006
DOI: 10.1200/jco.2005.03.2433
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Test for MLH1 and MSH2 Expression Predicts Clinical Outcome in Stage II and III Colorectal Cancer Patients

Abstract: Immunohistochemical testing for MLH1/MSH2 expression provides useful prognostic information for the management of stage II and III colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(134 citation statements)
references
References 58 publications
14
116
2
2
Order By: Relevance
“…Our finding of improved survival associated with MSI in colorectal carcinomas of any histologic subtype is consistent with previous reports [11][12][13]. This supports the recent WHO recommendation to grade mucinous carcinoma according to their MSI status [3].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of improved survival associated with MSI in colorectal carcinomas of any histologic subtype is consistent with previous reports [11][12][13]. This supports the recent WHO recommendation to grade mucinous carcinoma according to their MSI status [3].…”
Section: Discussionsupporting
confidence: 92%
“…Up to 15% of all colorectal carcinomas demonstrate MSI, more frequently secondary to acquired methylation of MLH1 (sporadic cases) than caused by a germline mutation in an MMR gene (Lynch syndrome). MSI has been reported to be a strong positive prognostic factor by multiple independent studies [11][12][13]. Some histologic subtypes of colorectal carcinomas are more commonly observed in MSI tumors, including medullary carcinomas, mucinous adenocarcinomas and signet ring cell carcinomas [14].…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite instability (MSI) of more than 40% frequently occurs in right-sided colonic cancer and carries better prognostic outcomes compared to microsatellite stable (MSS) tumors [11,26]. MA of the colon might have MSI, which would affect cancer recurrence and survival [26].…”
Section: Discussionmentioning
confidence: 99%
“…High microsatellite instability (MSI-H) in CRC has been linked to higher disease-free periods and overall survival (OS); therefore, adjuvant chemotherapy is not recommended for Stage II colonic adenocarcinoma with MSI-H [11]. Furthermore, conflicting data exist regarding the effect of body mass index (BMI) and smoking status on recurrence-free survival (RFS) in CRC patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] On the contrary, other studies have failed to come to the same conclusion and have suggested that MSI þ tumors may even have worse outcome or that they do not bear a prognostic value. [10][11][12][13] Possibly, the most reliable data are provided from a recent pooled molecular analysis on a randomized trial in patients with mainly stage II (and a few III) CRC who received either 5-fluorouracil (5-FU) adjuvant chemotherapy or surgery alone. It was found in that analysis that only MSIÀ tumors benefit from the addition of adjuvant 5-FU, and that administration of chemotherapy in stage II MSI þ patients may even be harmful.…”
Section: Genetic Abnormalities In Crcmentioning
confidence: 99%